1967
DOI: 10.1039/tf9676300824
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of internal rotation in chloroethanes

Abstract: Torsional frequencies have been assigned in the far infra-red and Raman spectra of C2H5C1, CH3. CHC12, CHzCl . CHzCI, CHCl2CH2C1, CH2Cl. Cc13, C H C l z . CHC12 and CHc12. CCl3. Barrier heights have been calculated for the symmetric top molecules ; V3 ranges from 3.3 to 14-2 kcalmole-1. The problem of estimating barriers in asymmetric top molecules is more difficult. Nevertheless, for these molecules, barrier heights ranging from 5.1 to 12-0 kcal mole-1 have been calculated, which are comparable in magnitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Neither the 222-cm-1 band reported by Allen et al 23 nor the 239-cm-1 band reported by Daasch et al 22 were observed in the Raman spectrum of the liquid. Neither the 222-cm-1 band reported by Allen et al 23 nor the 239-cm-1 band reported by Daasch et al 22 were observed in the Raman spectrum of the liquid.…”
Section: B Chachcbmentioning
confidence: 75%
“…Neither the 222-cm-1 band reported by Allen et al 23 nor the 239-cm-1 band reported by Daasch et al 22 were observed in the Raman spectrum of the liquid. Neither the 222-cm-1 band reported by Allen et al 23 nor the 239-cm-1 band reported by Daasch et al 22 were observed in the Raman spectrum of the liquid.…”
Section: B Chachcbmentioning
confidence: 75%
“…In these simulations, we included harmonic atom-atom forces, three-body harmonic angle potentials, and a four-body dihedral Ryckaert-Bellemans potential allowing torsion of the molecule around the C-C bond. 27,28,29 A MDS was performed during 150000 ps for the largest system (6400 molecules). We used this run in order to calculate the Kirkwood correlation factor.…”
Section: Molecular Simulationsmentioning
confidence: 99%
“…Vibrational and NMR studies on the pure solvent have shown that the C 2 H 3 Cl 3 molecules exist in both conformations 59 in the liquid phase, with comparable concentrations, 61,62,63,64 and that each conformer has a specific vibrational signature. 60,65 Given that two conformers are present in the solution used to form the solvate, it is possible that they are also present in the solvate; however, the occurrence and relative concentration of conformers varies according to the nature of the system, 66 and depends on the subtle balance of intramolecular strains and the effects of the molecular environment. 45 For example, the gauche conformer is energetically more stable and by far the most abundant in the gas phase, 65,60 where intermolecular interactions are negligible.…”
Section: Dielectric Relaxations and Raman Spectroscopy Resultsmentioning
confidence: 99%
“…60,65 Given that two conformers are present in the solution used to form the solvate, it is possible that they are also present in the solvate; however, the occurrence and relative concentration of conformers varies according to the nature of the system, 66 and depends on the subtle balance of intramolecular strains and the effects of the molecular environment. 45 For example, the gauche conformer is energetically more stable and by far the most abundant in the gas phase, 65,60 where intermolecular interactions are negligible. In the disordered solid phase of pure C 2 H 3 Cl 3 only…”
Section: Dielectric Relaxations and Raman Spectroscopy Resultsmentioning
confidence: 99%